2018
DOI: 10.1108/imefm-06-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

How individual’s characteristics influence financial inclusion: evidence from MENAP

Abstract: Purpose This study aims to analyze the financial inclusion of individuals living in the Middle East, North African, Afghanistan and Pakistan (MENAP). It intends to show the influence of these individuals’ characteristics on financial inclusion, using the World Bank Global Findex Database 2014 for 16 countries in the region. Design/methodology/approach A probit model is used to examine the marginal effect of financial inclusion of the characteristics of individuals living in the MENAP region. These characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 29 publications
13
32
0
3
Order By: Relevance
“…Previous research reviewed in this study deliberate on the extent of financial inclusion, its relationship with economic growth, financial sector development and the determinants of financial inclusion. Shihadeh (2018) analyzed how individual characteristics influence the intensity of financial inclusion in the MENAP regions, 7 it was found that women and poor people have less chance to be financially included as they are less likely to have an account with recognized financial institutions because of lesser job opportunities. Furthermore, informal financial institution with fewer rules and regulations and no collateral requirements make borrowing easier.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Previous research reviewed in this study deliberate on the extent of financial inclusion, its relationship with economic growth, financial sector development and the determinants of financial inclusion. Shihadeh (2018) analyzed how individual characteristics influence the intensity of financial inclusion in the MENAP regions, 7 it was found that women and poor people have less chance to be financially included as they are less likely to have an account with recognized financial institutions because of lesser job opportunities. Furthermore, informal financial institution with fewer rules and regulations and no collateral requirements make borrowing easier.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Banks, as financial intermediation institutions, have the main targets of earning profits, maximising stockholder value and minimising risk (Pilloff, 1996;Shihadeh et al, 2018). Therefore, banks that aim to achieve these targets on the supply side of their financial services depend on providing banking services to companies, SMEs, and retails on the demand side (Shihadeh, 2018). Further, the main issue for these demand-side entities is the investment and trading process that takes place when they seek the services financial institutions offer which, therefore, reflect on a country's economic and development sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied how socio-demographic characteristics shape the use of formal accounts (Allen et al, 2016;Fungáčová & Weill, 2014;Patwardhan, 2018;Shihadeh, 2018;Zins & Weill, 2016) and mobile money (Della Peruta, 2018;Gichuki & Mulu-Mutuku, 2018;Hasnain, 2017). In general, being a woman, poorer, and less educated tends to make someone less likely to use a formal account, and there is also a U-shape relationship with age.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%